An empirical comparative study of changing utilization pattern and problems of Rural and Urban Lakes of Gorakhpur, India - Singh, Alka; Sharma, Vishwambhar Nath (National Geographical Journal of India, 2022)
Lakes are the natural habitat of aquatic animals and plants. At the same time, it ensures the recharge of groundwater storage and also caters to the recreational and aesthetic requirements of people. A Lake can control surroundings temperature by keeping it fairly constant, this, in turn, can facilitate to support life forms. Balanced ecosystem enabled by lakes promotes not only healthy plants and animal communities but their clean water increases the security of animal nesting and resting places along with the livelihood of humans in its vicinities. Some of the losses (environmental degradation, extinction of species, etc.) occur through intentional exploitation of resources. Lakes are of value to humans in form of drinking water, agriculture, industry, livestock and energy generation; they become storage for flood water; sinks for sediment and contaminants to protect downstream areas and habitat for flora and fauna. Therefore, Lakes experience pressure of high population growth owing to human dependence on them. Economic uses, depleting factors and stewardship of urban and rural lakes are different. n Chilua lake, highest change during 1980 to 2019 was 65 per cent in dumping site followed by irrigation (61.66 per cent) and boating for person use whereas negative change was in washing site and use of water for cooking but it was different in Ramgarh Lake. During the above period Ramgarh Lake experienced highest positive change in dumping sites (88.34 per cent) followed by boating (40 per cent) for fishing and recreation while highest negative change was in cropping followed by cattle bathing. This study is a comparative assessment of economic and other utilities and problems of Ramgarh (urban) and Chilua (rural) lakes of Gorakhpur. The study is based on primary data collected from the surrounding dwellers of both lakes and supported by secondary data collected from different offices and laboratory-based investigations related to lakes